First Description of a Satellite DNA in Manatees’ Centromeric Regions - Valeri, Mirela Pelizaro; Dias, Guilherme Borges; do Espírito Santo, Alice Alves; Moreira, Camila Nascimento; Yonenaga-Yassuda, Yatiyo; Sommer, Iara Braga; Kuhn, Gustavo C. S.; Svartman, Marta (Frontiers in Genetics, 2021)
Trichechus manatus and Trichechus inunguis are the two Sirenia species that occur in the Americas. Despite their increasing extinction risk, many aspects of their biology remain understudied, including the repetitive DNA fraction of their genomes. Here we used the sequenced genome of T. manatus and TAREAN to identify satellite DNAs (satDNAs) in this species. We report the first description of TMAsat, a satDNA comprising ~0.87% of the genome, with ~684bp monomers and centromeric localization. In T. inunguis, TMAsat showed similar monomer length, chromosome localization and conserved CENP-B box-like motifs as in T. manatus. We also detected this satDNA in the Dugong dugon and in the now extinct Hydrodamalis gigas genomes. The neighbor-joining tree shows that TMAsat sequences from T. manatus, T. inunguis, D. dugon, and H. gigas lack species-specific clusters, which disagrees with the predictions of concerted evolution. We detected a divergent TMAsat-like homologous sequence in elephants and hyraxes, but not in other mammals, suggesting this sequence was already present in the common ancestor of Paenungulata, and later became a satDNA in the Sirenians. This is the first description of a centromeric satDNA in manatees and will facilitate the inclusion of Sirenia in future studies of centromeres and satDNA biology.